Peranan Sektor Kelautan dan Perikanan terhadap Pendapatan Asli Daerah (PAD) Kabupaten Fakfak - Randi Gandi Patiran (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the Outline of the State Direction in Chapter IV of the Sixth Phase of Five-Year Development, part F of the economic field point 2, it is said that